Ձևաբանական իրողությունները Մ. Սարգսյանի արձակում - Դ. Վ. Բախչինյան (ՀՀ ԳԱԱ հրատ.)
Для прозы М. Саргсяна характерно использование разговорных элементов, диалектизмов, а также своеобразное употребление существительных, прилагательных, глаголов, что создает особую стилистику как его речи, так и речи персонажей. The folk origins of language of M. Sargsjan are formed by means of morphological factors. In art prose of the writer are especially expressive grammatical parallels which are shown in the use of number, a case of a noun, degrees of comparison of adjective. Expressive possibilities of pronouns and verbs are also interesting.
Keywords: Philology; Linguistics; Language and Literature